Ullmann's Encyclopedia of Industrial Chemistry 2007
DOI: 10.1002/14356007.a20_181.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Phthalic Acid and Derivatives

Abstract: The article contains sections titled: 1. Phthalic Acid 2. Phthalic Anhydride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 204 publications
2
75
0
4
Order By: Relevance
“…It has been estimated that above 2 million tons/year worldwide of DEHP are produced. 1 Owing to the heavy use of phthalates around the world, phthalates are considered as universal environmental contaminants. DEHP can rapidly metabolized to its major metabolite mono (2-ethylhexyl)phthalate (MEHP) by pancreatic lipases in the lumen of guts following ingestion.…”
mentioning
confidence: 99%
“…It has been estimated that above 2 million tons/year worldwide of DEHP are produced. 1 Owing to the heavy use of phthalates around the world, phthalates are considered as universal environmental contaminants. DEHP can rapidly metabolized to its major metabolite mono (2-ethylhexyl)phthalate (MEHP) by pancreatic lipases in the lumen of guts following ingestion.…”
mentioning
confidence: 99%
“…It was found that the fresh leachate contained more components of acids and esters, phenolic compounds, and phthalates, with few aliphatic hydrocarbons and no aromatic hydrocarbons, aldehydes or silica containing compounds, which was different from the stabilized leachate in which all types of those components were found [2]. The xenobiotic organic compounds (XOCs) were commonly found in the landfill leachates [17]. Seven compounds were priority pollutants according to the USEPA [18] including p-Xylene, di-ethylphthalate (DEP), di-butyl phthalate (DBP), di-(2-ethylhexyl) phthalate (DEHP), naphthalene,1-methyl-, cresols, and bisphenol A.…”
Section: Resultsmentioning
confidence: 94%
“…Diesbezüglich konzentrieren sich die Forschungsbemühun-gen in erster Linie auf die Entwicklung hoch normal-selektiver Katalysatorsysteme. Die resultierenden linearen Aldehyde 2 bilden einen wertvollen Grundstock für die Synthese von Weichmachern, [2] wohingegen die verzweigten Produkte 2' wegen des Potenzials zur Generierung eines stereogenen Zentrums bei der Synthese von Pharmazeutika und Feinchemikalien von grçßerer Bedeutung sind. [3] Entdeckt wurde die Hydroformylierung 1938 vom deutschen Industriechemiker Otto Roelen.…”
Section: Allgemeines Und Hintergründeunclassified
“…[26] Schema 10. Generierung der katalytisch aktiven Spezies [h 5 -C 5 H 5 Ru(CO) 2 H] (14 a). [27] Abbildung 1.…”
Section: Angewandte Aufsätzeunclassified